PSO and Improved BSFS Based Sequential Comprehensive Placement and Real-Time Multi-Objective Control of Delta-Connected Switched Capacitors in Unbalanced Radial MV Distribution Networks - Su, X.; Masoum, M.; Wolfs, Peter (Institute of Electrical and Electronics Engineers Inc., 2015)
Delta-connected switched capacitors are common in three-wire MV distribution systems as found in Europe and Australia but the majority of past studies focus on star-connected capacitors as applied in North America. This study presents a comprehensive optimization based sequential strategy and a multi-objective optimization based real-time strategy for the optimal placement and control of delta-connected switched capacitors. Considering load variations, a comprehensive optimization for capacitor placement is formulated to maximize the net annual returns from network loss reduction and capacity release. A sequential strategy based on loss sensitivity analysis is presented for efficient capacitor placement on large-scale unbalanced distribution networks. Then a capacitor control strategy is proposed to simultaneously minimize network losses, voltage deviations and voltage unbalance factor (VUF) while a weighted sum method reflects the preferences on the mutually conflicting control objectives. For the mixed integer programming (MIP) problems of capacitor placement and control, an improved backward/forward sweep (BSFS) load flow based particle swarm optimization (PSO) method is used. Finally, the robustness of the proposed capacitor placement and control strategies are verified by comparison against existing popular schemes through detailed simulations over 24 h on a real unbalanced Australian MV network.